THERAPEUTIC APPLIANCE OF IMPERILED MEDICINAL PLANT PULLAS-RHODODENDRON ARBOREUM SM.: A SHORT PERIODICAL ANALYSIS FROM ANCIENT TO MODERN ERA - Santosh Kumar Thakur; Sumit Natthani; Mita Kotecha (International Journal of Ayurveda and Pharma Research, 2020)
Rhododendron arboreum Sm. the world’s most famous rhododendron, is known as national flower of Nepal. The word Rhododendron is derived from Greek word rhodo mean rose and dendron means tree. It is often called Rhodies. The flowers being sweet and sour taste are used in the preparation of squash, jams, jellies and local brew. It is used in folklore medicine to treat many disorders and often used as a substitute to another famous plant drug Rohitaka. Pharmaceuticals companies and traditional practitioners of Nepal are using its bark, as a substitute of Rohitaka i.e. Tecomella undulate (Sm.) Seem. The present review highlights some potential therapeutics from ancient to modern era in order to explore the gap as well as bring out certain suggestive approaches from exploration of its ancient traditional therapeutics/properties to future conservation of this plant species.